2003
DOI: 10.1002/elps.200305501
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic analysis of the cleaved form of serpin, squamous cell carcinoma antigen‐1 in normal and malignant squamous epithelial tissues

Abstract: The aim of this study was to detect the cleaved form of serine proteinase inhibitor (serpin), squamous cell carcinoma (SCC) antigen-1 in normal and malignant squamous epithelial tissues, which implies the presence of its target proteinase. The cleaved SCC antigen-1 in normal squamous epithelium was identified as a single spot with pI 6.35 and M(r) 40,000 by two-dimensional electrophoresis (2-DE) combined with immunoblotting. Interestingly, the cleaved form showed different biochemical properties in heat stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Characterization of a novel specific antibody, Pab Y2, by 2-DE combined with immunoblotting. Pab Y2 recognized intact forms of both SCCA1 and SCCA2 in normal cervical squamous epithelial tissue, but not the cleaved form of SCCA1 (arrow), which was detected by Mab 27, as reported previously (17).…”
Section: Identification Of Functional Scca1 and Scca2 On Nondenaturinsupporting
confidence: 84%
See 2 more Smart Citations
“…Characterization of a novel specific antibody, Pab Y2, by 2-DE combined with immunoblotting. Pab Y2 recognized intact forms of both SCCA1 and SCCA2 in normal cervical squamous epithelial tissue, but not the cleaved form of SCCA1 (arrow), which was detected by Mab 27, as reported previously (17).…”
Section: Identification Of Functional Scca1 and Scca2 On Nondenaturinsupporting
confidence: 84%
“…We used specific monoclonal antibodies, Mab 27 and Mab 426. We previously reported that Mab 27 reacted with both intact and cleaved forms of SCCAs, while Mab 426 reacted with cleaved forms of SCCAs, but not with intact SCCAs (17). To yield the novel antibody specific for intact forms of SCCAs, Pab Y2 was newly generated by immunizing with keyhole limpet hemocyanineconjugated to the synthetic peptide corresponding to a region from the C-terminal fragment of SCCA2 to rabbit and purified using the peptide affinity column.…”
Section: Two-dimensional Electrophoresis (2-de)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although SERPINB3/B4 protease substrates characterized in the in vitro systems are also inhibited by SERPINB3/B4 in cultured cells [28, 29], the structures of the interacting complex have not been crystallized and the interaction and related enzymatic kinetics study remain to be carried out under in vivo conditions.…”
Section: Biochemical Featuresmentioning
confidence: 99%
“…Apoptosis may be attenuated by SCCA1 to regulate cell death/proliferation balance [44]. As SCCA1 is largely found in squamous cells, it is not restricted to hepatocytes present in all tissues of body.…”
Section: Hepatitis B Virus Binding Protein (Hbv-bp)mentioning
confidence: 99%